2010
DOI: 10.1016/j.juro.2010.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Impact of Clinical Stage on Prostate Cancer Prognosis Among Contemporary Patients With Clinically Localized Disease

Abstract: Abbreviations and Acronyms AICPurpose: Clinical staging criteria for prostate cancer were established before the advent of widespread prostate specific antigen screening and extended biopsy templates. However, clinical stage remains commonly used in the modern era to predict prostate cancer outcomes. We hypothesize that in the context of data available from a contemporary biopsy, clinical stage no longer offers meaningful independent prognostic information for clinically localized prostate cancer. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…However, no statistical difference between both groups could be found regarding BCR rate. Reese et al reported that clinical stage in 4899 men who underwent RP for localized Pca was predictive for BCR on univariate, rather than multivariate, studies [18]. …”
Section: Preoperative Factorsmentioning
confidence: 99%
“…However, no statistical difference between both groups could be found regarding BCR rate. Reese et al reported that clinical stage in 4899 men who underwent RP for localized Pca was predictive for BCR on univariate, rather than multivariate, studies [18]. …”
Section: Preoperative Factorsmentioning
confidence: 99%
“…A minimal role of the clinical stage for risk stratifying has already been shown by Reese et al (11). The T stage could be less important than that established by D' Amico or other widely used risk groupings.…”
Section: Discussionmentioning
confidence: 90%
“…One study has shown that clinical T stage offers no independent information in predicting biochemical recurrence [32]. In addition, Gleason scoring has evolved over the years but there is still a lot of heterogeneity in grading, particularly for smaller volume tumors [33].…”
Section: J-cap Prospective Observational Study: Background Factors Ofmentioning
confidence: 99%